2022
DOI: 10.3390/sym14091939
|View full text |Cite
|
Sign up to set email alerts
|

Critical Dynamics in Stratospheric Potential Energy Variations Prior to Significant (M > 6.7) Earthquakes

Abstract: Lithosphere–atmosphere–ionosphere coupling (LAIC) is studied through various physical or chemical quantities, obtained from different sources, which are observables of the involved complex processes. LAIC has been proposed to be achieved through three major channels: the chemical, the acoustic, and the electromagnetic. Accumulated evidence supporting the acoustic channel hypothesis has been published, while atmospheric gravity waves (AGWs) play a key role in LAIC as the leading mechanism for the transmission o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…An external and occasional hazard that may affect the results, especially atmospheric analyses, is the eventual presence of extreme weather events, such as storms or hurricanes. In the literature, the identified pre-earthquake anomalies have been compared with hurricanes to exclude the ones probably not induced by earthquakes [96]. In the investigated time, NOAA reported several storms and hurricanes in the Atlantic Ocean sector (https://www.nhc.noaa.gov/data/tcr/index.php?season=2021&basin=atl, last access 10 March 2024) as reported in the following list.…”
Section: Discussionmentioning
confidence: 99%
“…An external and occasional hazard that may affect the results, especially atmospheric analyses, is the eventual presence of extreme weather events, such as storms or hurricanes. In the literature, the identified pre-earthquake anomalies have been compared with hurricanes to exclude the ones probably not induced by earthquakes [96]. In the investigated time, NOAA reported several storms and hurricanes in the Atlantic Ocean sector (https://www.nhc.noaa.gov/data/tcr/index.php?season=2021&basin=atl, last access 10 March 2024) as reported in the following list.…”
Section: Discussionmentioning
confidence: 99%
“…including VLF sub-ionospheric propagation data has been presented in detail in [Potirakis et al, 2021]. Also, newer studies using the NT time series method to other observable quantities of LAIC have shown existence of critical dynamics before EQs [Ghosh et al, 2021;Yang et al, 2020;Politis et al, 2022]. Furthermore, a very recent application of NT time series method to global seismicity is given by Christopoulos et al [2022].…”
Section: Natural Time Methodsmentioning
confidence: 99%
“…Such studies have revealed that different layers of the model reach critical state before a strong EQ occurrence. Specifically, the criticality analysis method called "natural time" (NT) analysis has successfully been applied to VLF subionospheric propagation data, ULF magnetic field data, global navigation satellite system deformation (GNSS) data, surface latent heat flux (SLHF) data and very recently in stratospheric potential energy ( ), as well to other EQ-related observables such as pre-EQ seismic electric signals (SES), foreshock seismicity, MHz fracto-EM Emissions, also known as fracto-EM Radiation, (FEME/FEMR), [e.g., Politis et al, 2021Politis et al, , 2022Potirakis et al, 2013Potirakis et al, , 2018aPotirakis et al, , 2021Yang et al, 2020;Ghosh et al, 2021;Varotsos et al, 2011, Eftaxias et al, 2018. Additionally, another criticality analysis method called "method of critical fluctuations" (MCF) has been also applied in VLF subionospheric propagation data, MHz FEME/FEMR recordings and ULF magnetic field data [Politis et al, 2021;Potirakis et al, 2016Potirakis et al, , 2018bPotirakis et al, , 2019Contoyiannis et al, 2004a].…”
Section: Introductionmentioning
confidence: 99%
“…The stratosphere is the altitude range between 10 km and 50 km above the ground, and wherein the atmosphere mainly flows at the horizontal direction. Within this altitude range, the air tends to be dry, resulting in steady movement and providing excellent visibility with low humidity [1]. Exploiting these favorable conditions, the stratospheric airship emerges as an extraordinary aerostatic vehicle capable of flying at extremely low speeds for extended durations.…”
Section: Introductionmentioning
confidence: 99%